AA MICRO BUSINESS EMPOWERMENT BY USING SOCIAL MEDIA - Kunto Inggit Gunwan; Mataji Mataji (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2022)
Since the enactment of the Asean Economic Community (MEA) at the end of 2015 should encourage all economic actors, including SMEs and Micro Enterprises, to improve themselves in order to improve the quality of production of both goods and services. If this is not done, then Indonesia is a